Shifting from Conventional to Organic Filter Media in Wastewater Biofiltration Treatment : A Review - Loh, Zhang Zhan; Nur Syamimi, Zaidi; Achmad, Syafiuddin; Yong, Ee Ling; Raj, Boopathy; Ahmad Kueh, Beng Hong; Dedy Dwi, Prastyo (MDPI, 2021)
Biofiltration is a promising wastewater treatment green technology employed to remove various types of pollutants. The efficiency of biofiltration relies on biofilm, and its performance is significantly influenced by various factors such as dissolved oxygen concentration, organic loading rate, hydraulic retention time, temperature, and filter media selection. The existing biofilters utilize conventional media such as gravel, sand, anthracite, and many other composite materials. The material cost of these conventional filter materials is usually higher compared to using organic waste materials as the filter media. However, the utilization of organic materials as biofilter media has not been fully explored and their potential in terms of physicochemical properties to promote biofilm growth is lacking in the literature. Therefore, this review critically discusses the potential of shifting conventional filter media to that of organic in biofiltration wastewater treatment, focusing on filtration efficiency-influenced factors, their comparative filtration performance, advantages, and disadvantages, as well as challenges and prospective areas of organic biofilter development.